Comparison of Attachment to Parents, Peers and Siblings in the Involved and Noninvolved Adolescents in Bullying - حلیمه بیابانی علی آباد; سمانه اسعدی; کاظم برزگر بفرویی (فصلنامه خانواده پژوهی, 2017)
The aim of this study was to compare attachment to parents, peers and siblings among involved (bulling, victim, and bulling-victim) and noninvolved in bullying in Yazd city. All of male and female students in the academic year 2013-2014 in Yazd included research population. A sample of 384 students were selected randomly through cluster sampling. Participants answered a sociometric questionnaire and also completed the Peer Relationship Questionnaire, the Inventory of Parents and Peer Attachment, and the Inventory of Siblings Attachment. Multivariate analysis (MANOVA) indicated that there were significant differences in attachment to parents, peers and siblings between involved adolescents in bulling and noninvolved ones (p>0/0001). Regarding the attachment to parents, peers and siblings, noninvolved group scored higher than the involved groups. Also, among involved groups, the bully and the victim- bully groups received higher scores in attachment to mother prior to the peer attachment. Finally, the attachment to siblings in both groups was the lowest scores of attachment.